Regional distribution of immigrants in Hungary - Tóth, Géza; Kincses, Áron (Hungarian Geographical Bulletin, 2010)
The purpose of this study is to analyse the territorial characteristics of foreign nationals those having migrated to Hungary. It is aimed to explore the triggers of choice of usual plan of residence and the differences by citizenship. Interrelationship between the proportion of migrants having resided in a particular area and the access by public road to it will be investigated with the help of path analysis. Firstly comparative studies on the geographical distribution of immigrants and that of former international migrants already settled in the country are to be conducted. Secondly the spatial disparities in the distribution of immigrants at micro-regional level will be identified by the potential method.